Surfactant-Enhanced In Situ Chemical Oxidation (S-ISCO®) - Lanoue, Meredith; Kessell, Lowell; Athayde, Gustavo (Águas Subterrâneas, 2011)
VeruTEK® Technologies, Inc. is a US-based international Green Chemistry technology company that has created an innovative solution to source zone contamination and NAPL plumes: Surfactant-enhanced In Situ Chemical Oxidation (S-ISCO®). S-ISCO involves the reactive transport of surfactants and oxidant systems to destroy contamination on site and in place, eliminating the need for excavation, for example, and providing timely and permanent solutions to soil, free-phase and dissolved contamination. During extensive laboratory and over 30 field implementations, including 18 full-scale remediations around the world, S-ISCO has remediated LNAPLs, DNAPLs and sorbed residuals, such as hydraulic fluid oil, PCBs and chlorinated solvents, and provided “complete or near complete destruction of coal tar NAPLs and residues.”4 VeruTEK continues to refine and expand its technology and applications through ongoing research and development, including partnerships with universities such as Yale and Carnegie Mellon, as well as the US EPA.